Analisis Penggunaan E-Commerce Terhadap Bisnis Usaha Mikro, Kecil, dan Menengah - Veronica Krisni Damayanti; Mulyadi Amin; Deden Sunandar (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Currently, e-commerce is increasingly in demand by various business groups, both large and small scale. This is due to the ease of promotion through online media or digital marketing, which makes it easier for business people to reach consumers to introduce or sell their products. This research aims to understand the impact of using e-commerce for MSME business actors. Data was collected through semi-structured interviews with MSME players who have used e-commerce to market their products. Data from these interviews were analyzed using the *thematic analysis* method which aims to identify patterns and find themes based on the data collected (Braun and Clarke, 2006). The research results show several categories related to the use of e-commerce by MSMEs, including individual abilities, reasons for not switching to other e-commerce platforms, as well as obstacles experienced such as infrastructure, technology, promotions, and unpleasant experiences faced by MSMEs when using e-commerce. commerce.